Symptomatic Atherosclerotic Non-acute Intracranial Vertebral Artery Total Occlusion: Clinical Features, Imaging Characteristics, Endovascular Recanalization, and Follow-up Outcomes - Zhao, Wei; Zhang, Jun; Meng, Yao; Zhang, Yuyan; Zhang, Jinping; Song, Yun; Sun, Lili; Zheng, Meimei; Wang, Wei; Yin, Hao; Han, Ju (Frontiers in Neurology, 2020)
Background and Objectives: Previous studies about symptomatic atherosclerotic non-acute intracranial vertebral artery total occlusion that was refractory to medical therapy were rare. We aimed to assess the clinical features, imaging characteristics, endovascular treatment feasibility and follow-up outcomes of these patients. Methods: Data of consecutive patients who had symptomatic atherosclerotic non-acute intracranial vertebral artery total occlusion and underwent endovascular recanalization from February 2016 to April 2020 were retrospectively collected in our prospective database. Clinical, imaging, procedural and follow-up data were collected and analyzed. Results: Thirty-one patients with male predominance were enrolled in this study. These patients presented with recurrent/progressive strokes in the posterior circulation despite maximal medical therapy. Angiographic analysis revealed asymmetric vertebral arteries due to unilateral hypoplasia, and the intracranial vertebral artery total occlusions occurred in the dominant vertebral arteries which were featured by long lesion length and high clot burden. The multiple infarctions and perfusion defects in the posterior circulation were demonstrated by the diffusion-weighted imaging and arterial spin labeling respectively. Successful endovascular recanalization was achieved in 87.1% of the patients. Over a median clinical follow-up duration of 11.0 months for the successful recanalization patients, 74.1% of the patients achieved favorable clinical outcomes (mRS score≤2). Conclusion: Symptomatic atherosclerotic non-acute intracranial vertebral artery total occlusion attributable to hypoperfusion is featured by the recurrent/progressive ischemic events, dominant intracranial vertebral artery total occlusion, long lesion length and high clot burden. Endovascular recanalization of the dominant intracranial vertebral artery occlusion appears to be a feasible treatment for these patients.